2004
DOI: 10.1207/s15374424jccp3304_14
|View full text |Cite
|
Sign up to set email alerts
|

Expressive Writing Intervention for Adolescents' Somatic Symptoms and Mood

Abstract: The effects of a widely used expressive writing intervention on adolescents' somatic symptoms, distress, and positive psychological functioning were evaluated. Eighth-grade (n=106) students were randomly assigned to write about either an emotional or a neutral topic for 3 consecutive days. Students completed measures of somatic symptoms, medical visits, distress, and positive functioning at baseline, postintervention, and 2 and 6 weeks later. Somatic symptoms and medical visits were unchanged as a result of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
2
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 33 publications
2
30
2
2
Order By: Relevance
“…Critically, however, there were no differences between the emotional and non-emotional writing groups, suggesting that focusing on emotional aspects of stressful events was no more beneficial for children than simply describing their daily activities. In contrast, Soliday, Garafolo, and Rogers (2004) found that 8th grade children who engaged in expressive writing showed decreases in distress 20 and 50 days after intervention. The conflicting results between these two studies may be due to differences in the ages studied, the timing of assessment, or both.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Critically, however, there were no differences between the emotional and non-emotional writing groups, suggesting that focusing on emotional aspects of stressful events was no more beneficial for children than simply describing their daily activities. In contrast, Soliday, Garafolo, and Rogers (2004) found that 8th grade children who engaged in expressive writing showed decreases in distress 20 and 50 days after intervention. The conflicting results between these two studies may be due to differences in the ages studied, the timing of assessment, or both.…”
mentioning
confidence: 75%
“…Indeed, Soliday et al (2004), who did find a decrease in distress as a result of expressive writing with 8th graders, included a shorter follow-up assessment. Again, Frattaroli's (2006) meta-analysis indicates that benefits are stronger for adults assessed sooner rather then later following expressive writing.…”
Section: Children's Narratives and Well-beingmentioning
confidence: 99%
“…We examined expressive writing, based on the work of Pennebaker (1997), in which participants write about issues of emotional significance in three sessions, on the basis that this activity has been found to improve negative affect in adolescents and adults (Koopman et al, 2005;Soliday, Garofalo, & Rogers, 2004). We included this control condition because we found that it did not result in significant decreases in negative affect relative to an assessmentonly control condition in a prior prevention trial (Stice, Shaw, Burton, & Wade, 2006).…”
Section: Expressive Writingmentioning
confidence: 99%
“…Communication by clients may help them to formulate their problems clearly and may even be of immediate value (I am grateful to an anonymous reviewer for this suggestion, in that writing about psychological difficulties has been shown to reduce distress in adolescents (Soliday et al, 2004) and may in itself be a therapeutic intervention).…”
Section: Opportunitiesmentioning
confidence: 99%